The correlates of smartphone use for transportation purposes in Egypt and Lebanon - Saber, Rania Elsayed; Dief-Allah, Dina M.; Ahmed, Nora Osama; Khalifa, Basma M.; Masoumi, Houshmand (Frontiers in Sustainable Cities, 2024)
The determinants of smartphone use for urban transportation purposes in developing countries, particularly in the cities of the Middle East and North Africa, have not been thoroughly investigated so far. This study aims to clarify the individual, mobility, and perception-related correlates of smartphone use specifically for ordering vehicles via ride-sourcing. in medium-sized and large cities as well as the megacities of the region. The four cities of Cairo and Alexandria in Egypt and Beirut and Jounieh in Lebanon were taken as case-study cities. An overall sample of 3,285 face-to-face interviews was undertaken between late 2022 and early 2023 using a questionnaire focusing on individual, household, mobility, and perceptions of the respondents. The following questions were answered in this study: are the levels of smartphone use for transportation purposes significantly different in the countries of Egypt and Lebanon? what are the correlates of smartphone use for transportation purposes in the four case-study cities? and what are the differences among the correlates of smartphone use for transportation purposes in the four case-study cities? The results of a Chi-square test of independence show that there is a highly significant difference between the smartphone use levels for transportation purposes among the four case-study cities: in subsamples in the Egyptian and Lebanese capitals, there is a stronger tendency to use smartphones for transportation. Moreover, the model fit based on Binary Logistic regression shows that age, trip generation for non-commute purposes, perceived ease of using ride-sourcing apps, perceived security when using public transportation, education status, and gender are significantly correlated with smartphone use. These explanatory variables function somehow differently in the case-study cities, but in general, there are strong similarities among the four cities. The results of this study can be used to reduce personal car use and strengthen shared mobility in the cities of the Middle East and North Africa region.